2012
DOI: 10.1158/1538-7445.am2012-503
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 503: Investigating the role of Tks5 and invadopodia in prostate tumor progression

Abstract: Much of the morbidity and mortality in prostate cancer patients occurs strictly in response to metastatic disease. While ongoing efforts are examining the therapeutic value of Src kinase inhibitors, the mechanism by which Src activates invasive cell behavior within the context of this disease are not well-understood. Invadopodia are cytoskeletal structures formed by cancer cells that enable binding to, proteolytic degradation of, and invasion through the extracellular matrix. We and others have previously demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, there is also evidence that does not support a causal association between serum IGF-I (or IGFBP-3, discussed below) and the risk of PCa (Woodson et al, 2003), and it was hypothesized that high-grade PCas are more autonomous and less sensitive to the action of IGF-I than low-grade cancers (Nimptsch et al, 2011). Moreover, the results from a recent study, which provides the largest assessment of the role of the IGF system in the development of prostate-specific antigen (PSA)-detected PCa, suggested that circulating IGF-I has a limited role in the development of early PCa but it may remain an important risk factor for disease progression (Rowlands et al, 2012). Furthermore, IGFBP-3 levels have been inversely associated with prostate carcinogenesis and the negative correlation between IGFBP-3 levels and cancer risk is consistent with a protective role of IGFBP-3, i.e., high IGFBP-3 concentrations may lead to reduced IGF-I bioavailability (Koutsilieris et al, 1995; Bogdanos et al, 2003; Papatsoris et al, 2005; Werner and Bruchim, 2009).…”
Section: Igf-i System and Its Involvement In Pca Biologymentioning
confidence: 99%
“…However, there is also evidence that does not support a causal association between serum IGF-I (or IGFBP-3, discussed below) and the risk of PCa (Woodson et al, 2003), and it was hypothesized that high-grade PCas are more autonomous and less sensitive to the action of IGF-I than low-grade cancers (Nimptsch et al, 2011). Moreover, the results from a recent study, which provides the largest assessment of the role of the IGF system in the development of prostate-specific antigen (PSA)-detected PCa, suggested that circulating IGF-I has a limited role in the development of early PCa but it may remain an important risk factor for disease progression (Rowlands et al, 2012). Furthermore, IGFBP-3 levels have been inversely associated with prostate carcinogenesis and the negative correlation between IGFBP-3 levels and cancer risk is consistent with a protective role of IGFBP-3, i.e., high IGFBP-3 concentrations may lead to reduced IGF-I bioavailability (Koutsilieris et al, 1995; Bogdanos et al, 2003; Papatsoris et al, 2005; Werner and Bruchim, 2009).…”
Section: Igf-i System and Its Involvement In Pca Biologymentioning
confidence: 99%